Creating the virtuous cycle with headless, hybrid, and low code : the principles of successful modern web apps - Northcutt, Ronald (O'Reilly Media, Inc., 2022)
With everyone looking for a silver bullet, each new technology, trend, or favored toolset promises to lead us out of the pain of development and into the utopia of perfection. Unfortunately, constant searching and striving for new ways to solve problems leads organizations and teams down the wrong path again and again, resulting in frustration, burnout, and wasted resources. The real secret? It's not about technology. It's about your approach. This report outlines the primary guidelines and patterns you need for building modern web applications, including when and where to apply technologies involved in the process. Author Ronald Northcutt helps software architects, developers, and IT leaders understand the underlying cycles at play, including how to evaluate solutions available today and in the future. Once you understand how to properly view problems, you'll learn how to place new technologies in the context of the proper mindset. The result is the ability to plan, build, and deliver successful applications that continue to improve and increase in value.